ALIRAN GAYA PELAT TANGGA KE BALOK-KOLOM: KOMPARASI SKEMA FREE-STANDING VS BEARING DAN EVALUASI KAPASITAS PELAT TANGGA PADA BEBAN GRAVITASI - Gischa Sandrina Aulia; Keisya Nairazzahra Abduloh; Y Djoko Setiyarto (CRANE: Civil Engineering Research Journal, 2025)
Construction sequence mismatches in stairwells often necessitate connecting stair slabs to the primary structure after it has already been erected. One practical on-site solution is the use of chemical anchors on the landing beam (edge beam), which interacts with the existing column. This study compares two behavioral schemes: (i) free-standing, where the stair slab spans between floor slabs without relying on the landing beam–column system; and (ii) bearing, where the slab edge rests on the landing beam anchored to the column. Numerical modeling was conducted using SAP2000, employing shell elements for the stair slab and link elements to represent joint stiffness. Gravity loads were defined according to SNI 1727:2020, while flexural–shear capacity evaluations of the slab followed SNI 2847:2019. The observed outputs included bending moment M11, shear V13, service deflection, link reactions, and local forces on the landing beam and column at the drilling zone. Comparative results show that the free-standing scheme reduces force transfer to the column but increases the demand on the stair slab; conversely, the bearing scheme decreases deflection and slab bending moments but raises anchor reactions and local column forces. In the case study, the design flexural capacity φMn of the slab approached but slightly fell below the demand Mu, while the serviceability deflection limit was satisfied. Therefore, the recommendation is conditional: the free-standing scheme is feasible if φMn ≥ Mu and deflection requirements are met; otherwise, slab strengthening or a shift to the bearing scheme with adequate anchor design is required. These findings provide a practical decision-making basis for projects involving non-monolithic stair connections.